Performing Internationalization of Higher Education in Canadian National Policy - Viczko, Melody; Tascón, Clara I (Canadian Journal of Higher Education, 2016)
Internationalization processes are at the fore of university strategic plans on a global scale. However, the work of internationalization is being performed through the connections between many actors at different policy levels. Our purpose here is to ask, what is happening with internationalization of higher education at the Canadian national policy level? To do so, we suggest that we must look at policies at the national level not as individual entities but rather as these policies exist in relation to each other. We examine three recent policy statements from different organizations at the national level in Canada: a federal governmental agency, a pan-Canadian provincial organization and a national educational association. Our approach involved mapping the actors, knowledges and spaces that are discursively produced through these texts and engaging a relational approach to policy analysis that questions what comes to be assembled as these policies co-exist in the national landscape.